2012
DOI: 10.1039/c2jm31126g
|View full text |Cite
|
Sign up to set email alerts
|

UV-initiated self-healing of oxolane–chitosan–polyurethane (OXO–CHI–PUR) networks

Abstract: These studies show that oxolane-chitosan-polyurethane (OXO-CHI-PUR) networks exhibit selfrepairing behavior upon exposure to UV light. Spectroscopic analysis revealed that molecular level processes responsible for the self-repairing mechanism of OXO-CHI-PUR networks are driven by free radical catalyzed polyurea-to-polyurethane conversion, formation of linear -C-O-C-segments via ring opening of OXO rings, as well as chair-to-boat conformational changes of glycosine units of the CHI backbone macromonomer. Incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Experimentally, lowering T g and moduli at the cut surfaces in self‐healable polyurethanes, which are able to recover after healing was observed. [2b,m,9a,91] Also, chain mobility increase inside the cut was also detected via laser speckle imaging (LSI) …”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, lowering T g and moduli at the cut surfaces in self‐healable polyurethanes, which are able to recover after healing was observed. [2b,m,9a,91] Also, chain mobility increase inside the cut was also detected via laser speckle imaging (LSI) …”
Section: Discussionmentioning
confidence: 99%
“…Later, Burnworth et al presented rubbery metallosupramolecular polymers with non-covalent metal-ligand motifs converting a UV light energy into heat to quickly and efficiently dissociate and heal the defects [15]. Ghosh et al observed lowering of Tg inside the scratch of damaged polymers, explained by a damage-induced chain scission and recombination reactions [16] and supported using molecular dynamics simulations [17].…”
Section: Introductionmentioning
confidence: 98%
“…A UV‐activated healing mechanism has been reported for PUs and PDMSs . These systems contain dynamic reversible bonds activated by UV exposure to repair damage.…”
Section: Introductionmentioning
confidence: 99%
“…[19] A UV-activated healing mechanism has been reported for PUs and PDMSs. [21][22][23] These systems contain dynamic reversible bonds activated by UV exposure to repair damage. UV-responsive polymers have also been used to form microcapsule shell walls.…”
Section: Introductionmentioning
confidence: 99%